What do the changing patterns of comorbidity burden in people living with HIV mean for long‐term management? Perspectives from European HIV cohorts. (3rd September 2020) - d'Arminio Monforte, A; Bonnet, F; Bucher, HC; Pourcher, V; Pantazis, N; Pelchen‐Matthews, A; Touloumi, G; Wolf, E
Abstract: Undoubtedly, comorbidities complicate long‐term HIV management and have significant cost implications for healthcare systems. A better understanding of these comorbidities and underlying causes would allow for a more considered and proactive approach to the long‐term management of HIV. This review examines cross‐sectional analyses of six European cohort studies (Athens Multicenter AIDS Cohort Study, Aquitaine Cohort, EuroSIDA Cohort study, French claims EGB, German InGef Cohort and the Italian Cohort of Individuals, Naïve for Antiretrovirals), which included individuals with HIV followed over a certain period of time. Based on these cohorts, we examined how comorbidities have changed over time; how they compromise HIV management; and how much of a financial burden they impart. These data also provided a framework to explore the major issues of ageing and HIV and the practical implications of managing such issues in real‐life practice.